Distribution and ecology of non-marine ostracods (Crustacea, Ostracoda) from Friuli Venezia Giulia (NE Italy) - Koen MARTENS; Fabio STOCH; Giampaolo ROSSETTI; Valentina PIERI (Journal of Limnology, 2009)
From August 1981 to July 2007, 200 inland water bodies were sampled to gather information on the Recent ostracod fauna of Friuli Venezia Giulia (NE Italy). A total of 320 samples were collected from surface, interstitial and ground waters. Whenever possible, ostracod identification was performed at species level based on the morphology of both valves and limbs. Seventy-four taxa in 30 genera belonging to 9 different families (Darwinulidae, Candonidae, Ilyocyprididae, Notodromadidae, Cyprididae, Limnocytheridae, Cytheridae, Leptocytheridae and Xestoleberididae) were identified. The maximum number of taxa per site was seven. The most common species was Cypria ophthalmica (133 records), followed by Cyclocypris ovum (86 records), C. laevis (49 records), Cypridopsis vidua (40 records) and Notodromas persica (28 records). Of particular relevance is the occurrence of six species new to Italy: Microdarwinula zimmeri, Penthesilenula brasiliensis, Fabaeformiscandona wegelini, Pseudocandona semicognita, Candonopsis scourfieldi, and C. mediosetosa. Scanning electron microscopy images of valves are provided for most of the described taxa. Geographical distribution of ostracods and their occurrence in relation to environmental variables were examined. The results of this study indicate that Friuli Venezia Giulia hosts a very diverse ostracod fauna, representing a significant proportion of all ostracod taxa known thus far from Italy.